A Qualitative Study of the Experiences of Patients with Knee Osteoarthritis Undergoing Moxibustion. Issue 1 (March 2013) - Son, Haeng-Mi; Kim, Duck Hee; Kim, Eunjeong; Jung, So-Young; Kim, Ae-Ran; Kim, Tae-Hun
Objective: To explore and understand how patients with knee osteoarthritis (OA) experience moxibustion. Method: This qualitative research was conducted as part of a larger clinical trial of the effectiveness of moxibustion for the treatment of knee OA by qualitative content analysis. Sixteen patients with mild knee OA who participated in a 12-week moxibustion treatment as part of the trial were interviewed using open-ended questions. Results: The participants recognised knee OA as a normal ageing process that caused physical and emotional discomfort in daily life. Regardless of any adverse effects of moxibustion, most of the participants were interested in continuous moxibustion treatment as a long-term management strategy and for general health. Conclusions: This study suggests that moxibustion can be helpful in managing symptoms related to knee OA. Patients' attitudes towards moxibustion can affect the treatment result and those who prefer it want to continue the treatment for a long time because they understand that knee OA is a chronic condition which needs continuous care. However, practitioners need to pay more attention to those who are very enthusiastic because they tend to endure treatment-related adverse events in their desire for better effects.